The Perakitan Alat Vacum Test ( NDT ) Di PT. Kintomo Engineering Group - Argyono Cahyono Adi; Ilham Arifin Pahlawan (Universitas Muhammadiyah Gresik, 2026)
This study discusses the assembly and testing process of a Vacuum Test device as part of a Non-Destructive Testing (NDT) method to detect leakage in welded joints. The project was carried out at PT. Kintomo Engineering Group, Gresik, aiming to understand the working principles, assembly procedures, and effectiveness of the Vacuum Test tool in industrial applications. The methodology included direct observation, technical participation, and structural simulation using Autodesk Inventor software. The test results showed that the assembled Vacuum Test device could reach a pressure of 50–100 mbar and effectively detect defects such as porosity and micro-cracks in weld joints. Simulation analysis indicated a maximum stress of only 0.613 MPa with a safety factor of 15, confirming that the tool is structurally safe for repeated use. These findings demonstrate that the Vacuum Test method is an effective and reliable visual inspection technique for detecting leakage without damaging the tested material